2014
DOI: 10.3324/haematol.2013.101071
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory human 6-sulfo LacNAc-positive dendritic cells accumulate in intestinal acute graft-versus-host disease

Abstract: LETTERS TO THE EDITOR © F e r r a t a S t o r t i F o u n d a t i o n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
1
9
0
2
Order By: Relevance
“…Contrary to our expectations, we could observe occasional slanDCs only in biopsy samples obtained from intestinal aGVHD, being undetectable in all the remaining tissue sections examined. It is worthy of note that the presence of slanDCs in intestinal biopsy specimens from aGVHD patients has been confirmed very recently in a series of colorectal aGVHD samples by immunohistochemistry (IHC) . In our opinion, the selective presence of slanDCs in intestinal aGVHD specimens could be related, similar to what has been observed in Crohn's disease , to a specific inflammatory pattern of aGVHD in the bowel.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Contrary to our expectations, we could observe occasional slanDCs only in biopsy samples obtained from intestinal aGVHD, being undetectable in all the remaining tissue sections examined. It is worthy of note that the presence of slanDCs in intestinal biopsy specimens from aGVHD patients has been confirmed very recently in a series of colorectal aGVHD samples by immunohistochemistry (IHC) . In our opinion, the selective presence of slanDCs in intestinal aGVHD specimens could be related, similar to what has been observed in Crohn's disease , to a specific inflammatory pattern of aGVHD in the bowel.…”
Section: Discussionsupporting
confidence: 70%
“…In our opinion, the selective presence of slanDCs in intestinal aGVHD specimens could be related, similar to what has been observed in Crohn's disease , to a specific inflammatory pattern of aGVHD in the bowel. In this latter tissue, slanDCs could also play an immunopathogenetic role, given their local expression of TNF‐α and IL‐23 and co‐localization with T cells .…”
Section: Discussionmentioning
confidence: 99%
“…Interessanterweise liegt in metastatischen Lymphknoten eine Kolokalisation von slanDCs mit NK-Zellen und neutrophilen Granulozyten vor. von slanDCs sind entzündliche Tonsillen [ 31,36 ] , das Ileum von Patienten mit Morbus Crohn [ 36 ] , die entzündete Synovia der rheumatoiden Arthritis [ 11 ] sowie die intestinale Graft-versus-Host-Disease [ 37 ] .…”
Section: Tumorerkrankungenunclassified
“…For example, in the HSCT treatment, donor‐derived CD4+ helper T cells and CD8+ cytotoxic T lymphocytes (CTLs) produce various inflammatory cytokines to lyse targeted cells in recipients, thus leading to GVHD. As functional antigen‐presenting cells (APCs), DCs facilitate this process by inducing and augmenting CD4+ helper T cells and CD8+ CTLs, whose number can increase rapidly in the lymph nodes during the early stage of transplantation and within 20 hours of continuous interaction with DCs . Furthermore, a recent study utilizing a syngeneic C57BL/6(B6) mouse stem cell transplantation model showed that due to the absence of functional APCs, certain cells derived from iPSCs survived without rejection when transplanted under the kidney capsule.…”
Section: Bidirectional Regulatory Mechanisms Of Dcs In Stem Cell Tranmentioning
confidence: 99%
“…As functional antigen-presenting cells (APCs), DCs facilitate this process by inducing and augmenting CD4+ helper T cells and CD8+ CTLs, whose number can increase rapidly in the lymph nodes during the early stage of transplantation and within 20 hours of continuous interaction with DCs. 14,15 Furthermore, a recent study utilizing a syngeneic C57BL/6(B6) mouse stem cell transplantation model showed that due to the absence of functional APCs, certain cells derived from iPSCs survived without rejection when transplanted under the kidney capsule. However, these cells co-transplanted with mature B6 DCs under the kidney capsule led to immune rejection.…”
Section: Bidirectional Regulatory Mechanisms Of Dcs In Stem Cell Trmentioning
confidence: 99%